PENGARUH PENGEMBANGAN KARIR DAN PEMBERIAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN HONORER DI SEKRETARIAT DAERAH KOTA SOLOK - Marlinda, Marlinda; Nasrah, Rasidah; Masri, Arfi (STMIK Pringsewu, 2024)
Based on an initial survey in the form of direct interviews with honorary employees at the Solok City Regional Secretariat, a condition was found where most employees felt less cared for in terms of compensation. Judging from the compensation given to them, it was felt that it was still lacking, such as direct compensation such as honorariums, incentives, and allowances given did not match what they expected, because there was a mismatch between the workload and the provision of honorariums, while indirect compensation in the form of vacation facilities, insurance, services and health were still less than satisfactory for employees, because superiors still paid less attention and the impact was that employees felt dissatisfied, while the agency had to achieve optimal results. The purpose of the study was to determine the effect of career development and compensation on the work productivity of honorary employees at the Solok City Regional Secretariat. This type of research uses descriptive with a quantitative approach. The data source used in this study was primary through the distribution of questionnaires regarding career development and compensation on employee work productivity. The sampling technique was carried out by total sampling, which was 88 people. The results of the study showed that partially career development had a positive effect on work productivity, the t-count value was greater than the t table, which was 5.272 1.9879, and the significant value was 0.000 0.05 and compensation had a positive effect on work productivity, the t-count value was also greater than the t table, which was 4.092 1.9879 and the non-significant value was 0.000 0.05. Based on the F test, the F-count value was 16.821 and the F-table value was 3.10. This states that simultaneously career development and compensation have a positive effect on work productivity of Honorary employees at the Solok City Regional Secretariat.